EKSTRAKSI SELULOSA BATANG TEMBAKAU SEBAGAI PERSIAPAN PRODUKSI BIOETANOL - Sri Seno Handayani; Amrullah Amrullah (Postgraduate, University of Mataram, 2018)
Nowadays the need for fuel has always improved as following the increase in community and industry activities. Therefore, we need to search for resources of alternative energy. The tobacco rod is one of the lignocellulosic materials which has three main components namely cellulose, hemicellulose and lignin. The production of bioethanol from lignocellulosic materials is strongly influenced by the composition of cellulose in its raw materials. This research use the cellulose extraction of tobacco rods by a bases method on NaOH concentrations are 2.5%, 5%, 7.5%, 10% and 12.5% (v/v) . The results show that the concentration of NaOH strongly influences the yield of cellulose extracted. The highest cellulose yield of the extraction is obtained on 12.5% of NaOH concentration.Keywords:Extraction, cellulose, tobacco rod, bioethanol